FAKTOR – FAKTOR YANG MEMPENGARUHI CASH HOLDING PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2013-2017 - Revita Romadhoni; Mahatma Kufepaksi; Ernie Hendrawaty (The Manager Review, 2019)
Cash holding is cash that must be available to the company to take certain actions in thefuture, decisions made by managers of non-banking companies in Indonesia will have animpact on the company's activities. The objective of this research is to analyze the effect ofBI rate, growth opportunity, leverage, firm size, board size, and profitability on cashholding, the research sample were 190 companies with 910 non-banking companies as theobservations on Indonesia Stock Exchange in 2013-2017. The statistical test used to testthe hypothesis is panel regression (fixed effects) with classical assumptions The result ofthis research shows that variable of BI rate, growth opportunity, and firm size has asignificant effect on cash holding at 5% significance level, and F test shows that BI rate,growth opportunity, leverage, firm size, board size, and profitability simultaneously affectsthe cash holding as 82%. This research also shows that the variables that affect the cashholding of all non-banking companies on the Indonesia Stock Exchange (IDX) use a tradeofftheory.